MICROENCAPSULATION TECHNIQUES: A COMPREHENSIVE REVIEW - VENKATACHALAM, CHITRA DEVI; Susithraa R D; Abhinayasree N; Mohamed Asfaque S; Sathish Raam R; Mothil S (Food and Feed Research, 2025)
Microencapsulation technology consists of wrapping protective layers around bioactive compounds in the form of microcapsules varying in size ranges between 1-1000 µm. This approach encapsulates heat-sensitive ingredients, shielding them from temperature shifts, pH changes, and light, ensuring their controlled release for a variety of pharmaceutical and food uses. This technology can enhance the bioavailability, stability, and organoleptic characteristics of functional compounds such as flavonoids, carotenoids, vitamins and lipophilic nutrients (e.g., PUFA from fish oil). This review focuses on a complex review of microencapsulation technologies, including coacervation, spray drying, emulsification, fluid bed coating, freeze-drying, complex coacervation and solvent evaporation extrusion-based encapsulation and electrospinning-based encapsulation. All methods differed in the particle size, hydrophobicity and solubility, as well as the porosity of the microcapsules. Selecting a suitable technique depends on the properties of core materials and wall materials. Furthermore, the paper explains the influence of encapsulation methods on product functionality, flavor masking, and the enhancement of physical and thermal properties, emphasizing their significance in the evolving food industry.